Respon Allelopati Gulma Ageratum conyzoides dan Borreria alata terhadap Pertumbuhan dan Hasil Tiga Varietas Kedelai (Glycine max) - Kilkoda, Abdul Karim (Jurnal AGRO, 2015)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">P<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">enelitian ini <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">bertujuan <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">untuk menguji pengaruh eksudat akar gulma Ageratum conyzoides dan Borerria<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">alata<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">yang <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">didalamnya <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">terkandung <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">alelopati <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">t<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">anin dan <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">f<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">enol <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">terhadap pertumbuhan dan hasil tiga varietas kedelai berdasarkan ukuran benih kedelai. Percobaan dilaksanakan <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">di Rumah kaca <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Fakultas Pertanian Universitas Padjadjaran, Jatinangor<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Kabupaten Sumedang, Jawa Barat<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">pada bulan September <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: SV; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="SV">2014. <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="SV"> <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Penelitian disusun dalam Rancangan Acak Lengkap factorial. Faktor pertama adalah ekstrak kasar gulma, yaitu; <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">EG0 = ekstrak gulma 0 g/100 ml<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">(kontrol)<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">, <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">EG1 = ekstrak gulma (Ageratum + Borreria)<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">100 (g/v)<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">, <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">EG2 = ekstrak<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">gulma (Ageratum + Borreria)<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">200 (g/v)<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">, <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">EG3 = ekstrak gulma (Ageratum + Borreria) 300 (g/v)<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">, faktor kedua yaitu <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">ukuran bobot dan jenis kedelai<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">; <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">K<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">1 = varietas Gepak<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.05pt; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN"> Kuning<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> (bobot 100 biji : 6,82 gram) ukuran bobot kecil, <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.25pt; mso-font-width: 105%; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">K<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.25pt; mso-font-width: 105%; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.25pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> = varietas <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.25pt; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">Gema<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">(bobot 100 biji : 12 gram) ukuran bobot sedang, <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">K<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">3 = varietas <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">Grobogan<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> (bobot 100 biji : 17,8 gram) ukuran bobot besar. Tidak terdapat interaksi antara ekstrak kasar gulma dengan <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">ukuran bobot dan jenis kedelai<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> terhadap seluruh parameter pertumbuhan dan hasil yang diamati. Terdapat pengaruh mandiri antar sesama varietas kedelai hampir pada semua parameter pertumbuhan dan hasil tanaman kedelai, kecuali parameter luas daun, dengan nilai tertinggi dihasilkan oleh varietas <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">Grobogan<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">yang memiliki ukuran biji besar. <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-font-kerning: 11.0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Terdapat pengaruh mandiri dari ekstrak kasar gulma <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">Ageratum conyzoides<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN"> dan Borerria<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">alata<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> pada semua parameter pertumbuhan dan hasil tanaman kedelai. <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This study aimed to examine the effect of root exudates of weeds Ageratum conyzoides and Borerria alata therein containing tannins and phenols as allelopathy on growth and yield of three soybean varieties with concern to size of the seed. The experiment was conducted in greenhouse of Faculty of Agriculture, Universitas Padjadjaran, Jatinangor Sumedang, West Java in September 2014. The study was set in completely randomized design factorial. First factor was the weed crude extract, namely; EG0 = weed extract 0 g / 100 ml (control), EG1 = weed extract (A. conyzoides + B. alata) 100 (g / v), EG2 = weed extract (A. conyzoides + B. alata) 200 (g / v), EG3 = weed extract (A. conyzoides + B. alata) 300 (g / v). Second factor was and type of soybean; K1 = variety Gepak Kuning (weight of 100 seeds: 6.82 gram) weight size small, K2 = variety Gema (weight of 100 seeds: 12 gram) weight size medium, K3 = variety Grobogan (weight of 100 seeds: 17.8 gram) weight size big. There was no interaction between weed crude extract and soybean type. Meanwhile, there was independent effect among varieties tested for almost all parameters observed, except for leaf width. There was also independent effect from crude extract of Ageratum conyzoides and Borerria alata on all growth and yield parameters of soybean. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> RESPON ALLELOPATI GULMA Ageratum conyzoides DAN Borreria alata TERHADAPPERTUMBUHAN DAN HASIL TIGA VARIETAS KEDELAI (Glycine max) <w:LsdException Locked="false" Priority="70" SemiHidden="false" UnhideWhenUsed="false" Name="Dark List